2018
DOI: 10.1177/0194599818776633
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Patients: Rates, Reasons, and Risk Factors for 30‐Day Unplanned Readmission

Abstract: Objective To analyze rates, risk factors, and complications for 30-day readmission among head and neck cancer (HNC) patients. Methods Retrospective review of administrative records from Vizient (Irving, Texas) Clinical Data Base/Resource Manager on HNC patients who underwent a head and neck surgical procedure from January 2013 through September 2015 at 176 academic and community medical centers. Results Of the 18,121 patients included in the study, 2502 patients were readmitted within 30 days (13.8%). Mean tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…The detected readmission predictors 1) head and neck cancer, 2) higher comorbidity, and 3) non-surgical cases have also been shown to be relevant for US-American otolaryngology patients treated following the introduction of healthcare quality programs like the National Surgical Quality Improvement Program (NSQIP) [6, 9, 1416]. High-volume departments had also a higher overall readmission rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detected readmission predictors 1) head and neck cancer, 2) higher comorbidity, and 3) non-surgical cases have also been shown to be relevant for US-American otolaryngology patients treated following the introduction of healthcare quality programs like the National Surgical Quality Improvement Program (NSQIP) [6, 9, 1416]. High-volume departments had also a higher overall readmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…Readmission was planned in 4.9% and unplanned in 2.8% of the cases (Surgical cases alone: 2.6%). Former studies were mainly focused on surgical cases: Here, 30-day unplanned readmission rates vary from 5% to 20% [1417]. The highest rates in otolaryngology patients are reported for head and neck cancer patients, especially following laryngectomy [15, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the readmission rate widely differs between types of cancer and different chemotherapy regimens. For example, previous studies have reported 22% readmission rate among patients with gastrointestinal cancers, 13.8% among patients with head and neck cancer, 4.3% among those who underwent lung cancer surgery and 52% in those who received etoposide, ifosfamide, and cisplatin [5, 19, 20]. To the best of our knowledge, ours is the first study of its kind in cancer patients who received cisplatin-based chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 85%
“…To date, there have been many studies investigating short‐term morbidity and mortality associated with head and neck cancer surgeries, including TL. Such studies have investigated factors associated with need for reoperation, 11,12 30‐day unplanned readmission, 13‐18 30‐day mortality, 19 and prolonged inpatient LOS. Those investigating LOS include reviews of institutional 20 and national database 16,19,21 .…”
Section: Introductionmentioning
confidence: 99%